Peranan Bank Pusat Islam dalam melaksanakan polisi kewangan - Anuar, Abdul Rahim (Universiti Utara Malaysia, 1989)
The Central Bank in an Islamic economy through its monetary policies is responsible in determining that the growth of money supply is not too rapid or too slow but sufficient to exploit the economic potentials fully so that the production of goods and services would not only increase individual welfare and prosperity to the society but also that of the ummah as a whole.